Inflammation and ER Stress Downregulate BDH2 Expression and Dysregulate Intracellular Iron in Macrophages - Susu M. Zughaier; Brandon B. Stauffer; Nael A. McCarty (Journal of Immunology Research)
Macrophages play a very important role in host defense and in iron homeostasis by engulfing senescent red blood cells and recycling iron. Hepcidin is the master iron regulating hormone that limits dietary iron absorption from the gut and limits iron egress from macrophages. Upon infection macrophages retain iron to limit its bioavailability which limits bacterial growth. Recently, a short chain butyrate dehydrogenase type 2 (BDH2) protein was reported to contain an iron responsive element and to mediate cellular iron trafficking by catalyzing the synthesis of the mammalian siderophore that binds labile iron; therefore, BDH2 plays a crucial role in intracellular iron homeostasis. However, BDH2 expression and regulation in macrophages have not yet been described. Here we show that LPS-induced inflammation combined with ER stress led to massive BDH2 downregulation, increased the expression of ER stress markers, upregulated hepcidin expression, downregulated ferroportin expression, caused iron retention in macrophages, and dysregulated cytokine release from macrophages. We also show that ER stress combined with inflammation synergistically upregulated the expression of the iron carrier protein NGAL and the stress-inducible heme degrading enzyme heme oxygenase-1 (HO-1) leading to iron liberation. This is the first report to show that inflammation and ER stress downregulate the expression of BDH2 in human THP-1 macrophages.